2014
DOI: 10.1016/j.jss.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecule-1 mediates murine colon adenocarcinoma invasion

Abstract: Background Intercellular adhesion molecule-1 (ICAM-1) modulates cell–cell adhesion and is a receptor for cognate ligands on leukocytes. Upregulation of ICAM-1 has been demonstrated in malignant transformation of adenomas and is associated with poor prognosis for many malignancies. ICAM-1 is upregulated on the invasive front of pancreatic metastases and melanomas. These data suggest that the upregulated ICAM-1 expression promotes malignant progression. We hypothesize that the downregulation of ICAM-1 will mitig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Hyperinsulinemia increases colon cancer cell resistance to 5-fluorouracil [ 31 ], and oxaliplatin chemotherapy [ 31 , 32 ], and exposure to insulin promotes colonic tumor multiplicity [ 33 ]. sICAM-1 is associated with obesity and hyperinsulinemia [ 34 ], and exposure to sICAM-1 stimulates tumor growth [ 35 ], and the inhibition of sICAM-1 attenuates colonic tumor cell invasion [ 36 ]. These in vivo and preclinical data are supported by prospective cohort studies that suggest higher BMI and visceral obesity [ 16 , 18 ], hyperinsulinemia [ 17 ], and elevated sICAM-1 [ 37 ] are associated with recurrence and survival among patients with colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinemia increases colon cancer cell resistance to 5-fluorouracil [ 31 ], and oxaliplatin chemotherapy [ 31 , 32 ], and exposure to insulin promotes colonic tumor multiplicity [ 33 ]. sICAM-1 is associated with obesity and hyperinsulinemia [ 34 ], and exposure to sICAM-1 stimulates tumor growth [ 35 ], and the inhibition of sICAM-1 attenuates colonic tumor cell invasion [ 36 ]. These in vivo and preclinical data are supported by prospective cohort studies that suggest higher BMI and visceral obesity [ 16 , 18 ], hyperinsulinemia [ 17 ], and elevated sICAM-1 [ 37 ] are associated with recurrence and survival among patients with colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that upregulation of ICAM-1 has been demonstrated in different malignant tumors including liver cancer, esophageal cancer, renal cell carcinoma, squamous carcinoma, gastric cancer or pancreatic cancer and associated with poor prognosis (14,15,(19)(20)(21)(22).Under inflammatory environment, TGF (transforming growth factor) promoted osteosarcoma cell metastasis through the increasement of ICAM-1 by Akt signal pathway (23). Downregulation of ICAM-1 by short hairpin RNA (shRNA) transduction methods mitigated mouse colon cancer cell MC38 invasion ability (24). Proto oncogene K-ras could increase ICAM-1 expression in pancreatic acinar cells and the formation of precancerous lesions (25).…”
Section: Discussionmentioning
confidence: 99%
“…The biologic pathways through which exercise may reduce the risk for disease recurrence and premature mortality have not been elucidated. Endothelial cell-adhesion molecules including sICAM-1 and sVCAM-1 have emerged as therapeutic targets, 22,23 given their implication in promoting the growth of existing micro-metastases and the formation of new micro-metastases through circulating tumor cell differentiation, cell-cell adhesion and dissemination via activation of the PI3K-Akt-mTOR pathway. 16 We hypothesized that exercise would reduce sICAM-1 and sVCAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…16 Concentrations of sICAM-1 and sVCAM-1 increase with disease stage, 17,18 and elevated concentrations of sICAM-1 and sVCAM-1 are independently associated with disease recurrence and premature death among colon cancer survivors. 1721 sICAM-1 and sVCAM-1 have been recommended as therapeutic targets, 22,23 and represent novel pathways through which exercise may reduce the risk of disease recurrence among colon cancer survivors.…”
Section: Introductionmentioning
confidence: 99%